An optimised version of the secretome protein enrichment with click sugars (SPECS) method leads to enhanced coverage of the secretome. Issue 5 (31st January 2017) - Serdaroglu, Alperen; Müller, Stephan A.; Schepers, Ute; Bräse, Stefan; Weichert, Wilko; Lichtenthaler, Stefan F.; Kuhn, Peer‐Hendrik
Abstract : The secretome, the entirety of all soluble proteins either being secreted or proteolytically released by a cell, plays a key role in inter‐cellular communication of multi‐cellular organisms. Pathological alterations contribute to diseases such as hypertension, cancer, autoimmune disorders or neurodegenerative diseases. Hence, studying disease‐related perturbations of the secretome and the secretome itself covers an important aspect of cellular physiology. We recently developed the secretome protein enrichment with click sugars (SPECS) method that enables the analysis of secretomes of in vitro cell cultures even in the presence of FCS with MS. So far, SPECS facilitated the identification of protease substrates of BACE1, SPPL3 and ADAM10. Though, the SPECS method has already enabled deep insights into secretome biology, we aimed to improve the SPECS protocol to obtain even more information from MS‐based secretome analysis and reduce the amount of input material. Here, we optimised the reaction buffer, the pH and replaced Dibenzocyclooctyne (DBCO) PEG12‐biotin with the more water‐soluble variant DBCO‐sulpho‐biotin to finally provide an optimised protocol of the recently published SPECS protocol. Overall, the number of quantified glycoproteins and their average sequence coverage was increased by 1.6‐ and 2.4‐fold, respectively. Thus, the opzimised SPECS protocol allows reducing the input material by half without losing information. These improvements make the SPECS method more sensitive and more universal applicable to cell types with limited availability.